Analysis of Need Response to the Development of E - Magazine on Static Fluid Material at Bengkulu City High School - Cahya Widya Gunawan; Eko Risdianto; Desy Hanisa Putri (IJOEM: Indonesian Journal of E-learning and Multimedia, 2022)
The purpose of this work is to analyze the needs of teachers and students for learning media from electronic magazines for high school students about static fluid material. The research data was taken from physics teachers and also students of class XI of SMA N 1, SMA N. 6, SMA N 7 PLUS Bengkulu city. The data sources used in this study were obtained from physics teachers and 139 XI class students. This research method is a descriptive study included in the Department of Research and Development (RND). The research and development phases used are based on the ADDIE model, i.e. analysis, planning, development, implementation and evaluation. The research phase used the needs analysis phase, where tools such as school observation, interview and needs surveys were used. Data analysis techniques using quantitative data analysis and qualitative analysis. The results of this study indicate that the instrument used is valid and reliable. The results of this study also show that high school students and teachers strongly agree that they need learning environments based on electronic magazines.